PENGEMBANGAN MODUL DATA KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Lase, Agnes Lestariani (Universitas Nias Raya, 2023)
The purpose of this study was to develop a group data module to improve mathematical problem solving skills. The type of research is research and development (R&D), with a 4D model (define, design, development, disseminate). Data collection techniques are questionnaires, and tests. Data analysis techniques are qualitative data analysis and quantitative data analysis. Based on research and discussion that the validation test results from the validator show that it is very valid, the content aspect validator is 75% valid category, the language aspect validator is 100% very valid category, the didactic or presentation aspect validator is 90% very valid category and the display or graphic aspect validator by 89.5%. The results of the practicality test of the module from the limited class student respondents with an average of 78.2 in the practical category, and the module practicality test results from the field class student respondents with an average of 94.22 in the very practical category. The results of the effectiveness of the limited class trial module with an average score of 41.4 in the moderately effective category, and the effectiveness of the field class trial with an average score of 70.3 in the effective category. The developed module is used to improve mathematical problem solving skills in group data material.